Cryptography with Layered Algorithms for Text Security on Android - Safrianti, Ery; Fitriansyah, Fernanda (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2020)
Android phone is one of the most widely used telecommunications devices today. The exchange of various forms of information ranging from text, sound, images and video through this media is inseparable from the threat of criminal crime through digital data theft. Data security aspects are very important to be considered, one of which is data in the form of text. Text data is commonly used in short message services (SMS), chat in various Android applications or in the use of logins and passwords. This research will create an application on Android for securing text data through cryptographic techniques with a layered algorithm using three types of algorithms namely Caesar, Blowfish and AES Algorithms (Advanced Standard Encryption). This application can run on Android 5.0 (lollipop) or above, which can be used to encrypt and decrypt text messages. The test results show that the results of the initial text that was encoded through the encryption process can be safely returned by the decryption process without the slightest mistake with the original text. The encryption test for capital letters, numbers, and punctuation can be completely decrypted.